2014
DOI: 10.3201/eid2002.131126
|View full text |Cite
|
Sign up to set email alerts
|

Anncaliia algeraeMicrosporidial Myositis

Abstract: Immunosuppression is a risk factor for serious infection in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 35 publications
(73 reference statements)
1
38
0
Order By: Relevance
“…In resource‐limited settings, where the specific genus of microsporidia may not be identified, triple combination therapy should be given to cover all potential microsporidial species. A recent publication from Australia reported a similar observation in a patient who was given albendazole, sulfadiazine, and pyrimethamine and survived, whereas a patient who did not receive this regimen died . We observed that, in the absence of appropriate antimicrobial treatment, the disease progresses rapidly over a period of weeks to produce quadriparesis and esophageal involvement before death.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In resource‐limited settings, where the specific genus of microsporidia may not be identified, triple combination therapy should be given to cover all potential microsporidial species. A recent publication from Australia reported a similar observation in a patient who was given albendazole, sulfadiazine, and pyrimethamine and survived, whereas a patient who did not receive this regimen died . We observed that, in the absence of appropriate antimicrobial treatment, the disease progresses rapidly over a period of weeks to produce quadriparesis and esophageal involvement before death.…”
Section: Discussionsupporting
confidence: 74%
“…− This phenomenon may be due to the rarity and lack of awareness of this disease involving the muscles; therefore, the diagnosis may not be suspected clinically. A recent publication from Australia reported an antemortem diagnosis of microsporidial myositis in 2 rheumatoid arthritis patients …”
Section: Discussionmentioning
confidence: 99%
“…; Watts et al. ; Weiss ). It was shown by experiments that a broad range of hosts including gammarids easily acquired A. algerae infection after per oral or per cutaneous experimental challenge with spores (Becnel et al.…”
Section: Discussionmentioning
confidence: 99%
“…In subsequent years, the incidence of Microsporidia has declined dramatically in response to better management of HIV infection with improvement in cellular immunity. However, awareness of the importance of microsporidian infections has again been raised through the recognition that transplant recipients and patients undergoing immunosuppressive therapy for illnesses such as rheumatoid arthritis may be vulnerable to infection (119)(120)(121)(122). There is also evidence that decline in CD8 levels has been linked to infection (123).…”
Section: Stains For the Microsporidiamentioning
confidence: 99%